Miranda's waning protections : police interrogation practices after Dickerson - White, Welsh S., 1940- (University of Michigan Press, 2001)
"Of all the Supreme Court's criminal cases, its decision in Miranda v. Arizona has been the most controversial. When the case was decided in 1966, conservatives expressed the fear that law enforcement would be irreparably harmed because Miranda would significantly diminish the possibility of convicting a suspect on the basis of his confession. Over the past three decades, scholars, as well as those associated with law enforcement, have attacked Miranda on both constitutional and policy grounds. When the Supreme Court reaffirmed Miranda in United States v. Dickerson on June 26, 2000, conservatives complained about that decision's adverse impact on law enforcement. Liberals, on the other hand, hailed the decision as a reaffirmation of individual rights."